The Complementarity of Public and Private Capital and the Optimal Rate of Return to Government Investment - Ogura, Seiritsu; Yohe, Gary (Quarterly Journal of Economics, 1977)
I. Optimal government investment under distortion, 653.—II. An application: Corporate income taxation, 656.—III. The impact of depreciation, 661.—IV. Concluding remarks, 662.